Rethinking retirement in Greece: flexible pathways, gaps and policy implications - Konstantinidou, Danai; Koumarianos, Evangelos (Ревија за социјална политика/Journal of Social Policy, 2025)
Population ageing, evolving labour markets, and concerns over financial sustainability have placed increasing pressure on pension systems across Europe. In response, many countries have introduced flexible retirement pathways that allow individuals greater choice in how and when to retire. This paper examines the design and implications of flexible retirement pathways in Greece. It maps the available options, outlines the corresponding financial incentives and disincentives, and analyses their expected impacts. To deal with demographic pressures and fiscal challenges, Greece has implemented extensive pension reforms, with the primary aim of raising effective retirement ages and encouraging longer working lives to enhance the long-term financial sustainability of the pension system. These reforms have shaped the currently available flexible retirement pathways, such as deferred retirement, early retirement with benefit reductions, and the possibility of combining pensions with income from work.Evidence indicates a gradual increase in the effective retirement age, higher employment rates among older groups, and a rise in employed pensioners, highlighting a shift toward extending labour market participation. Flexible retirement options have likely contributed to this development, although broader reforms have also played a substantial role in increasing the effective labour market exit age. However, little is known about the distributional effects of flexible retirement in Greece or the motivations behind individual choices. Barriers remain, including limited awareness, administrative complexity, and weak financial literacy, highlighting the importance of transparency and accessible information to support informed decision-making.
Keywords: flexible retirement, Greece, pensions